The Effect of Work Compensation, Work Discipline and Work Environment on Increasing Employee Productivity at Suzuya Mall Rantauprapat - Bunga Pebriani; Pitriyani Pitriyani; Nova Jayanti Harahap (Quantitative Economics and Management Studies, 2023)
Employee productivity refers to the level of output or efficiency of an employee in carrying out his work duties within a certain period of time. It is an important factor for the success of an organization because it directly affects the quality and quantity of jobs produced, which in turn affects the competitiveness, profitability and sustainability of the organization. Employee productivity is influenced by various factors, including work compensation, work discipline and work environment. Effective management of these factors can increase employee productivity, leading to improved organizational performance. The purpose of this study was to determine and analyze the effect of work compensation, work discipline and work environment on increasing employee performance at Suzuya Mall Rantauprapat. This research is a type of association research. The method used in this research is descriptive statistical method with a quantitative approach, the sampling technique used in this research is a questionnaire. Data collection techniques using data instrument tests, and statistical tests. The results of this study indicate that work compensation positively affect the performance of Suzuya Mall Rantauprapat, work discipline positively affect the performance of Suzuya Mall Rantauprapat, and work environment positively affect the performance of Suzuya Mall Rantauprapat.